Polyneuropathy, Myocardial Dysfunction and Pericardial Effusion Following Duodenal Switch - Mouallem, Meir; Margolin, Moran Livne; Friedman, Yehudit Eden; Blankenfeld, Hadas (Acta medica (Hradec Kralove), 2018)
Duodenal Switch procedure is a type of bariatric surgery that was reserved for severely morbid obese people. Patients undergoing this procedure are at high risk for nutrient deficiencies. In this report we present a case of a patient who had developed polyneuropathy, generalized muscle weakness, Wernicke encephalopathy, myocardial dysfunction and pericardial effusion six years following this operation. He was treated by multivitamins and trace elements with a complete resolution of all of these disturbances. The patient was fully rehabilitated.
Keywords: perikardiální efuze; Polyneuropathies; Bariatric Surgery; Humans; Wernicke Encephalopathy; Vitamins; vitaminy; bariatric surgery; Muscle Weakness; dospělí; polyneuropatie; stopové prvky; lidé; myocardial dysfunction; svalová slabost; Obesity, Morbid; Adult; Postoperative Complications; pooperační komplikace; polyneuropathy; Male; Pericardial Effusion; morbidní obezita; Trace Elements; bariatrická chirurgie; mužské pohlaví; Wernickeova encefalopatie; pericardial effusion